Tribological studies of epoxy-carbon nanofiber composites – Effect of nanofiber alignment using AC electric field. (October 2019) - Chanda, Amit; Sinha, Sujeet K.; Datla, Naresh V.
Abstract: In this study, an electric field was applied to align carbon nanofibers (CNF) in an epoxy matrix and the tribological performances were evaluated. The epoxy/aligned CNF composites were fabricated with different weight percentages of non-functionalized CNFs (0.2–2 wt%) with which friction and wear tests were carried out keeping sliding direction normal to fiber orientation. The wear resistance of 1 wt% random and aligned composites improved by 3.5 and 25 times, respectively, compared to pure epoxy (20 N load). Moreover, the friction coefficient reduced from 0.6 for pure epoxy to 0.44 and 0.24 for random and aligned CNF/epoxy composites, respectively. Improved thermal stability, normal load carrying capacity and lubricating effect of CNFs contributed to the superior wear resistance of aligned composites. Graphical abstract: Image 1 Highlights: Carbon Nanofibers (CNF) were aligned across thickness within epoxy matrix using AC electric field. Aligned CNF/epoxy composites showed significantly less friction coefficient and wear rate. Better normal load carrying capacity, thermal stability and lubricating effect of CNFs led to superior wear resistance.